Characterization of bovine dentine derived hydroxyapatite (BDHA) structures - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2011)
Hydroxyapatite (HA, Ca10(PO4)6(OH)2), the main mineral component of bones and teeth, is among the leading biomaterials being an ideal material for grafting purposes in orthopedic and dental applications. The HA bioceramics can be naturally derived or synthetically produced. The synthetic HAs are reliable, but their production is usually complicate and expensive. To develop natural bioceramics seems to be a more economic way. The aim of this study was to develop a novel natural HA from bovine tooth dentine material. For this purpose, bovine teeth were calcined and the enamel was separated from dentine. Dentine parts were ball milled and pressed to green compacts. Those compacts were sintered at 1000, 1100, 1200 and 1300°C. Compression strength, microhardness, and density measurements along with SEM and X-ray diffraction analyses were conducted. From those results (e.g. microhardness was 346HV for sintering at 1300°C) it was seen that bovine dentine derived HA (BDHA) is an interesting and reliable source of HA for producing biomaterials.
Keywords: Bovine dentine derived hydroxyapatite; Hydroxyapatite; Mechanical properties